2023
DOI: 10.3389/fnsys.2023.1100505
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in glutamate AMPA receptor subunits mRNA with fast gating kinetics in the mouse cochlea

Abstract: Evidence shows that females have increased supra-threshold peripheral auditory processing compared to males. This is indicated by larger auditory brainstem responses (ABR) wave I amplitude, which measures afferent spiral ganglion neuron (SGN)-auditory nerve synchrony. However, the underlying molecular mechanisms of this sex difference are mostly unknown. We sought to elucidate sex differences in ABR wave I amplitude by examining molecular markers known to affect synaptic transmission kinetics. Alpha-amino-3-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(81 reference statements)
2
2
0
Order By: Relevance
“…However, there have been many investigations about the relationship between sex and hearing thresholds in mice in regards to age-related hearing loss and other noise-induced damage. Some of these studies present no differences in acoustic acuity between sexes in young pre-clinical mice [33,34,35] that align with our ABR measurements in the J:DOs, while other experiments suggest inherent variability linked to sex [36,37,38,39,40]. Whether there is a difference between males and females seems to depend on the mouse strain tested.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, there have been many investigations about the relationship between sex and hearing thresholds in mice in regards to age-related hearing loss and other noise-induced damage. Some of these studies present no differences in acoustic acuity between sexes in young pre-clinical mice [33,34,35] that align with our ABR measurements in the J:DOs, while other experiments suggest inherent variability linked to sex [36,37,38,39,40]. Whether there is a difference between males and females seems to depend on the mouse strain tested.…”
Section: Discussionsupporting
confidence: 80%
“…A comparable observation can be made in C57BL/6 mice, but only at > 100 days of age [37], at an age of 50 days the measurements of both sexes were nearly identical [41]. Young C57BL/6J mice tested at the age of 37 days display no significant difference between male and female [33]. In B6CBAF1/J mice, a cross between C57BL/6 and CBA/J, only the highest measured frequency, 32 kHz, shows a small but statistically significant lower threshold for female mice [42].…”
Section: Discussionsupporting
confidence: 70%
“…Representative genes associated with the biological processes identified in the female-dominant clusters included TFAP2B , which showed a 2-fold increase, CNTN1 , which had a 2.9-fold increase, and the glutamate receptor GRIA2 , and doublecortin DCX genes, which showed 8-fold higher levels in female as compared with male cells ( Figure 3C ). While DCX is an X chromosome–encoded gene, GRIA2 is encoded on chromosome 4 with sex differences in expression in cochlea ( 30 ) and the brain ( 31 ). These sex-specific differences were, in general, independent of the insulin sensitivity status (compare dark- vs. light-shaded squares and circles in Figure 3C ) and occurred in vitro in the absence of sex hormones, i.e., represented cell-autonomous sex-specific changes in gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has revealed that CI results in a reduction of synaptic AMPAR in the hippocampus ( Chang et al, 2006 ). Specifically, in the cochlea, AMDAR is primarily located in the nerve endings near the base of the IHCs ( Hong et al, 2018 ), Furthermore, in the cochlea, AMDAR plays a crucial role in mediating rapid excitatory transmission at mature spiral ganglion neurons SGNs afferent synapses ( Lozier et al, 2023 ). Interestingly, changes in the subunit composition of synaptic AMDAR occur as a result of HL, leading to long-term effects on synaptic integration ( Pilati et al, 2016 ).…”
Section: Hypothesismentioning
confidence: 99%